Posted by **mark** on Monday, February 26, 2007 at 4:11pm.

(2w-1)^2=4(w-3)^2

Expand both sides of the equation, then simplify:

4w^1 - 4w + 1 = 4w^2 - 24w + 36

......

.....

w = 7/4

## Answer This Question

## Related Questions

- math - I need help figuring out these two questions on euations with integers. -...
- Math - Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + ...
- Algebra - Solve S=a/(1-r) for r S = a/(1-r) Multiply both sides by 1-r S*(1-r...
- Math - 4(j)-7=9 Add 7 to both sides of the equation and you get 4 j = 16 Now ...
- maths - i have to make y the subject of this equation: 4t + 7y - 9 = 0 wod it be...
- math - Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T ...
- Math - Simplify: 24w^7t^4/6w^9t^2 And How Exactly do u do this? I got 4w^16t^6
- Find the sum of thuis question - Can someone find the sum for this equation ...
- Algebra - Which of the following describes a correct method for solving the ...
- MATH PLEASE CHECK IT!!2 - m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m...

More Related Questions